Into action to improve women's work and health - Kindenberg, Ulla; Karlsson Gadea, Ingemar (Stockholm, 2003)
"This publication gives a glimpse into the rich fields of research and experience at the congress Women Work & Health held in Stockholm, Sweden, 2-5 June, 2002. Here you can find examples of concrete applications of research as well as descriptions of the work to improve women's health and working conditions around the world. It is our hope that the publication will be of practical use to researchers and practitioners alike."